ANALISIS WAKTU KERJA DAN KEBUTUHAN JUMLAH OPERATOR UNTUK MEMENUHI TARGET PRODUKSI DI PT. XYZ - Ana Faiqotul Himmah; Sajiyo Sajiyo (Industrika : Jurnal Ilmiah Teknik Industri, 2022)
PT. XYZ is a company engaged in manufacturing metal or iron plate processing. The problem being faced is that the company does not plan for the right number of operators. This causes the production target is not met because it has limited human resources. In the working time analysis, the standard time results are 108,33 seconds or 1,8 minutes each unit. Based on the Work Load Analysis (WLA), the average workload at each work station is 90%. However, there are several work stations that have excessive workloads such as leg cutting work stations by 209%, blanking legs by 135%, ovens by 137%. The proposal given is to provide additional workloads on work stations that have a moderate workload. The cost of materials needed for the manufacture of stove stoves is 60.000 units each month, with a total cost of Rp1.021.236. Then for the regular cost of Rp1.920.000 each worker. The initial overtime fee uses 3 hours of overtime, which is Rp16.114.682. Keywords: Cost, Number of Operators, Work Load Analysis, Standard Time